La coherencia lingüística de los documentos en occitano cispirenaico aragonés del siglo XIII - Santomá Juncadella, Luis (Revista de Filología Románica, 2008)
The repopulation of the pyrenean kingdom of Aragon by frank immigrants coming predominantly from Occitany, meant the utilization of an aragonese cispyrenean occitan dialect, mainly in the city of Jaca, its first capital, where, in this dialect, were written the first documents in romance up to the beginning of the XIV century. The internal linguistic coherence of the three known sets of documents is analyzed, as well as the different estyles present in each of them, which result in an acceptable representation of the different verbal paradigma for the whole documentary corpus. Coherence between the three documentary sets, from the point of view of phonetics and of grammatical morphological categories is, with a few exceptions, confirmed. The main discrepancies appear in connection with past perfect verbal paradigma and in the presence of diphthong |ie| in oclusive velar plus nasal ended verbal roots of tenir and uenir verbs. From this follows, that the documentary corpus content, is enough in order to define the linguistic characteristics of aragonese cispyrenean occitan dialect.